Peculiarities of changes in indices of immunological reactivity in experimental allergic alveolitis under adrenalin myocardial injury and their correction with thiotriazoline - Volodymyr Pyndus (Journal of Education, Health and Sport, 2015)
Pyndus Volodymyr. Peculiarities of changes in indices of immunological reactivity in experimental allergic alveolitis under adrenalin myocardial injury and their correction with thiotriazoline = Особливості змін показників імунологічної реактивності при експериментальному алергічному альвеоліті в умовах адреналінового пошкодження міокарда та їх корекція тіотриазоліном. Journal of Education, Health and Sport. 2015;5(10):185-190. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32603